Allatotropin modulates myostimulatory and cardioacceleratory activities in Rhodnius prolixus (Stal) - Villalobos Sambucaro, María José (2015)
Haematophagous insects can ingest large quantities of blood in a single meal and eliminate high volumes of urine in the next few hours. This rise in diuresis is possible because the excretory activity of the Malpighian tubules is facilitated by an increase in haemolymph circulation as a result of intensification of aorta contractions combined with an increase of the anterior midgut peristaltic waves. It has been previously described that haemolymph circulation during post-prandial diuresis is stimulated by the synergistic activity of allatotropin (AT) and serotonin in the kissing bug Triatoma infestans; resulting in an increase in aorta contractions. In the same species, AT stimulates anterior midgut and rectum muscle contractions to mix urine and feces and facilitate the voiding of the rectum. Furthermore, levels of AT in midgut and Malpighian tubules increased in the afternoon when insects are getting ready for nocturnal feeding. In the present study we describe the synergistic effect of AT and serotonin increasing the frequency of contractions of the aorta in Rhodnius prolixus. The basal frequency of contractions of the aorta in the afternoon is higher that the observed during the morning, suggesting the existence of a daily rhythmic activity. The AT receptor is expressed in the rectum, midgut and dorsal vessel, three critical organs involved in post-randial diuresis. All together these findings provide evidence that AT plays a role as a myoregulatory and cardioacceleratory peptide in R. prolixus.